Two dimensional Laplace’s equation in Cartesian
Co-ordinates.
Let us consider a wave function ψ . Where ψ = ψ
( x , y )
Then the Laplace’s equation
can be written as
s
2 ψ = 0
Or in other words we
can write as
(
∂ 2 ψ / ∂ x 2 ) + ( ∂ 2 ψ / ∂ y 2 )
= 0 _ _ _ _ _ _ _ ( 1 )
Therefore
Ψ(
x , y ) = X ( x ) Y ( y )
The equation ( 1 ) can
be written as
[
( ∂ 2 / ∂ x 2 ) ( X Y ) ] + [ ( ∂ 2 / ∂ y 2
) ( X Y ) ] = 0
Y
(∂ 2 X / ∂ x 2 ) + X (∂ 2 Y / ∂ y 2 )
= 0
(
1 / X ) ( ∂ 2 X / ∂ x 2 ) + ( 1 / Y ) ( ∂ 2 Y /
∂ y 2 ) = 0
(
1 / X ) ( ∂ 2 X / ∂ x 2 )
= - ( 1 / Y ) ( ∂ 2 Y / ∂ y 2 )
L. H. S. is depends only on the variable ‘ x ’
and R. H. S. is depends only on variable ‘ y ’. This is true only when
(
1 / X ) ( ∂ 2 X / ∂ x 2 )
= - ( 1 / Y ) ( ∂ 2 Y / ∂ y 2 ) = λ
Therefore
(∂
2 X / ∂ x 2 ) = λ X
&
-
(∂ 2 Y / ∂ y 2 ) = λ Y
This can be written as
(
∂ 2 X / ∂ x 2 ) - λ X = 0 _ _ _ _ ( 2 )
&
(
∂ 2 Y / ∂ y 2 ) + λ Y = 0 _ _ _ _ ( 3 )
These equations can be
solved by ordinary differential equations
Let us consider equation no (2)
(∂
2 X / ∂ x 2 ) - λ X = 0
[
( ∂ 2 / ∂ x 2 ) – λ ] X = 0
D
2 – λ = 0
Where
D 2 = [ ( ∂ 2 / ∂
x 2 )
D
= ± ( λ ) 1/2
Hence the most general
form of above equation can be written as
X
= C e ( λ ) ½ x + D e - ( λ ) ½ x _ _ _ _ ( 4 )
Let us consider
equation no ( 3 )
(
∂ 2 Y / ∂ y 2 ) + λ Y = 0
[(∂
2 / ∂ y 2 ) + λ ] Y = 0
D
2 + λ = 0
Where
D 2 = [ ( ∂ 2 / ∂ y 2 ) ]
D2
= - λ
D
= ± i ( λ ) ½
The solution of above
equation can be given as
Y
= A cos ( λ ) ½ y + B sin ( λ ) ½ y _ _ _ _ ( 5 )
Thus the general
solution of Laplace’s equation can be written as follows
Ψ
( x , y ) = X ( x ) . Y ( y )
Where X ( x ) is given
by equation ( 4 ) and Y ( y ) is given by equation ( 5 )
Ψ ( x , y ) = {[ C e ( λ ) ½ x + D e -
( λ ) ½ x ] [A cos ( λ ) ½ y + B sin ( λ ) ½ y ]}
No comments:
Post a Comment